Study on mechanical properties of stud connectors in steel-lightweight aggregate concrete composite structures. (January 2023) - Liu, Lei; Zhang, Long; Zhu, Li; Li, Jian; Yang, Yifan; Hao, Lin
Abstract: To systematically study the factors affecting the shear bearing capacity of lightweight aggregate concrete stud connectors, six groups of 12 push-out specimens were made to investigate the concrete type, stud diameter, concrete strength and stirrup spacing. The effect of stirrup spacing on the shear performance of lightweight aggregate concrete stud connectors was analyzed in detail by using finite element modeling analysis. The load-slip curve equation and the shear bearing capacity equation with stirrup ratio factor were proposed for the lightweight aggregate concrete stud connectors through the experimental value and the finite element analysis value, respectively. The test results show that the shear bearing capacity of lightweight aggregate concrete stud connectors increases with increasing stud diameter, with stud diameter having a greater influence on stud connector shear bearing capacity. The shear bearing capacity of lightweight aggregate concrete stud connectors increases with increasing concrete strength, and the influence of concrete strength on the bearing capacity is low. The shear bearing capacity of lightweight aggregate concrete stud connectors decreases with increasing stirrup spacing, and the influence of stirrup spacing on the bearing capacity is lower. The theoretical shear stiffness calculated by the load-slip curve formula and the shear bearing capacity calculation formula proposed in this paper are more consistent with the test shear stiffness when the cut line slope is set to 0.2 mm. This research is critical for the promotion and use of lightweight aggregate concrete stud connectors in bridge engineering.